Cerebral nocardiosis: case report and literature review - L. Šalaševičius; R. Kvaščevičius (Neurologijos seminarai)
Background. Cerebral nocardiosis is a very rare opportunistic infection of the brain, accounting for only up to 2% of all cerebral abscesses. Nocardial infections are most common among immunocompromised patients, although there are reports of nocardiosis in immunocompetent patients as well. Diagnosis is difficult, because nocardiosis is insidious in its clinical course, there are no specific laboratory or clinical findings, and the complete diagnosis is often reached only after bacteriological culture tests of the pus obtained during surgical excision. Case report. In this article we report a case of cerebral nocardiosis in 80-year old male with no immunodeficiency. Nocardiosis was diagnosed only with microbiological culture test after the surgical intervention. Conclusions. Diagnosing cerebral nocardiosis is difficult and the treatment is long-term and aggressive. In this case, a radical surgical excision of the cerebral abscess was performed and the treatment of possible primary odontogenic site of infection and a long-term (21 months) antibiotic therapy with Biseptol (Trimethoprim – Sulfamethoxazole) were initiated, resulting in complete recovery and return to good quality of life.